Adult education in the age of artificial intelligence: the human resource development perspective - Osolase, Ehikioya Hilary; Mohd Rasdi, Roziah; Mansor, Zuraina; Qi, Kou (Human Resource Management Academic Research Society, 2024)
As the future of teaching, learning, and workplace environment changes due to the evolution and advancement of artificial intelligence (AI) and interconnected technologies, it is required that human resource development (HRD) scholars and practitioners intervenes for a successful transition. In deploying the use of narrative review technique, which led to the evaluation of several related literatures published between 1988 and 2024 in various academic and professional platforms and connected to the study’s objective, this article brings forth a new perspective which was able to interconnect the fields of HRD with that of adult education (AE) and AI. In spite of global affirmation which acknowledges HRD as a field and practice whose expertise is responsible for the development of new knowledge and reskilling of adult educators and learners, in addition to the workforce, HRD is yet to contribute to the scholarly discourse linking AE to AI in the age of digitalising learning and education, which is because of the need to adapt to new technologies through continuous enhancement of learning and development. As its intervention will help in the transformation of adult pedagogy to be in tune with today’s and tomorrow’s learning and work environments. With the expertise of HRD, the capabilities of adult educators and the knowledge of learners will be developed, with the intention that theoretical and practical knowledge and competencies on AI technologies will be acquired by all stakeholders in the AE domain. As a proactive discipline with a multidisciplinary outlook which transcends the social and management sciences, it is necessary to utilise its know-how for promoting awareness and developing new competencies on AI technologies among adult educators and learners, as this is required for seamless transition on integrating AI into AE teaching and learning curriculum. Through this method, AE educators and learners will have their knowledge on Fourth Industrial Revolution (4IR) technologies developed and continuously improved, being that they are products from a generation whose knowledge on automated teaching and learning practices is limited. An intervention from HRD could possible be through its activities such as training and development for developing awareness and reskilling, talent development for remodeling abilities and competencies to become innovative and align with current and future expectations, in addition to career development focused on increasing performance and productivity, etcetera. Resulting to a paradigm shift from traditional or manual AE approaches, to that which embraces digitalised education and prepares everyone with vested interest for the future. Additionally, as a result of the changing nature of the workplace environment, this will help to reskill and upskill adult educators and learners who are competing with the workforce from Generation Z and Alpha born into the era of advanced technologies. Aside these contributions, the implications for HRD research, theory, and practice was discussed. Future studies using empirical data from qualitative, quantitative, or mixed-method, can further investigate this study’s objective. This could be among educational institutions, service industries and those in the manufacturing sectors, or small and midsize enterprises (SMEs), revealing how HRD expertise and activities is being utilised for preparing AE educators and learners along with the general workforce for the future of teaching and learning. As the outcome from such investigation may perhaps reveal intriguing facts which could not be captured in this present study. Finally, this study provided a summary of its conclusion.